802.3-2022/Cor 1-2024 - IEEE Standard for Ethernet - Corrigendum 1 - Multi-Gigabit Automotive Medium Dependent Interface (MDI) Return Loss (IEEE, 2025)
This corrigendum to IEEE Std 802.3-2022 corrects the MDI Return Loss specification for MultiGigabit Automotive Physical Layer entities (PHY) in Clause 149 and Clause 165.
Keywords: Automobiles -- Design and construction.; Local area networks (Computer networks)